Effect of Accounting Understanding, Information Technology Use, and Education Level on the Quality of Financial Reports with Human Resource Competency as a Moderated Variable - Ramadhani, Mesra Amalia; Budiwitjaksono, Gideon Setyo; Sulistyowati, Erna (PT FORMOSA CENDEKIA GLOBAL, 2024)
With human resource competency serving as a moderating element, the purpose of this study is to examine the impacts of accounting expertise, information technology utilization, and educational attainment on the quality of financial reports. This inquiry employs a quantitative methodology. A sample of 120 cooperative financial managers was given a questionnaire to complete in order to collect data in the Lamongan District. The study makes use of SmartPLS 3.0. The study's conclusion implies that an individual's level of education, accounting expertise, and use of information technology all have an impact on the caliber of financial reports. Meanwhile, the impact of accounting knowledge, information technology use, and educational attainment on the caliber of financial reporting cannot be mitigated by human resource expertise.